‘Do Not Go Through the System Passively’: Integrating Environmental Studies and Ethnic Studies Through a Social Justice Outdoor Education Program for High School Learners - Laura Moorhead; Jeremy Jiménez (Youth)
This study examines a social-justice-focused environmental education program serving marginalized students through fostering engagement with local communities and natural environments. It presents a focused ethnographic case study of teachers of color who designed and implemented an ethnic studies and environmental education curriculum intended to address the educational alienation experienced by many students as well as the intersection of social justice and environmental stewardship. The study considers how teachers at two very different urban schools—one a continuation school, the other a traditional college preparatory high school—provided a venue for students to advocate on behalf of oppressed communities with which they identified. Researchers collected qualitative data from a variety of sources: field notes from participant observation of outdoor and classroom activities, document review of curriculum and student projects, focus group interviews with 86 students, and semi-structured individual interviews with teachers and alumni. Students in this innovative program did not fit the classic climate justice activist profile by engaging in climate marches, raising money for environmental organizations, or lobbying Congress for better environmental legislation. However, a key finding from the program and the teachers who lead it is to broaden our understanding of what it means to be a climate activist.